LATE SAXON AND VIKING ART - Kendrick, T. D. (Thomas Downing) ([S.l.])
1 online resource
Keywords: Late Saxon and Viking Art (1949) is a lavishly-illustrated examination of the art of the Saxon era - the carvings, sculpture, illustrations, drawings and paintings that emerged from the Anglo-Saxon and Viking cultures.